An azobenzene-based photochromic liquid crystalline amphiphile for a remote-controllable light shutter - Kim, Dae-Yoon; Lee, Sang-A; Kim, Huisu; Kim, Soo Min; Kim, Namil; Jeong, Kwang-Un (ROYAL SOC CHEMISTRY, 2015)
By considering intramolecular conformations and intermolecular interactions, an azobenzene- based photochromic liquid crystalline amphiphile is synthesized for demonstrating a remote-controllable light shutter by the photo-induced isothermal phase transition between the highly ordered crystal phase and the isotropic liquid phase.
Keywords: PHOTOCHEMICALLY REVERSIBLE LIQUEFACTION; CARBOXYLIC-ACID COMPOUNDS; PHASE-TRANSITIONS; SOLIDIFICATION; TRANSFORMATION; ORGANIZATION; DERIVATIVES; SHAPE